2016
DOI: 10.1055/s-0042-108853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relation between Vitamin D and Serum Omentin and Vaspin Levels in Women

Abstract: Vitamin D may affect the release of adipokines from the adipose tissue, and this effect may be in a negative or positive manner. This effect of vitamin D may probably be mediated via vitamin D receptors exhibited in the adipose tissue, or via mechanisms not identified yet. The results of this study suggested that there was a significant, positive correlation between serum vitamin D levels and vaspin, whereas a significant, negative correlation between vitamin D levels and omentin. Further studies on larger ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…According to these findings, it can be assumed that Another finding of the present study is the linear relationship between omentin-1 and vitamin D. Circulating vitamin D was found positively correlated with omentin-1. Unlike our findings, Zorlu et al reported an inverse correlation between serum levels of omentin-1 and vitamin D in healthy women [22]. The participants in Zorlu et al's study were younger and probably in the premenopausal period.…”
Section: Discussioncontrasting
confidence: 99%
“…According to these findings, it can be assumed that Another finding of the present study is the linear relationship between omentin-1 and vitamin D. Circulating vitamin D was found positively correlated with omentin-1. Unlike our findings, Zorlu et al reported an inverse correlation between serum levels of omentin-1 and vitamin D in healthy women [22]. The participants in Zorlu et al's study were younger and probably in the premenopausal period.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies show that omentin‐1 has insulin‐sensitizing effects , while visfatin activates the insulin receptor and MCP‐1 deficiency ameliorates insulin resistance . Associations have been reported between 25(OH)D and these markers in studies of healthy women and women with polycystic ovary syndrome , but not in pregnant women. Thus, further investigation of these relationships in pregnancy is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation had no significant effect on vaspin levels, however, a cross sectional study indicated that serum vaspin and vitamin D have negative correlation (Zorlu et al, ). We could not find any clinical trials in the literature evaluating the effect of vitamin D treatment on vaspin concentrations (Moradi, Mirzaei, Abdurahman, Keshavarz, & Hossein‐nezhad, ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaspin (visceral adipose tissue‐derived serine protease inhibitor) is a kind of adipocytokines secreted from visceral and subcutaneous white adipose tissues (Hida et al, ) Vaspin sensitizes insulin receptors and it has been shown that its serum levels can increase in the consequence of insulin resistance and obesity (Kovacs, Blüher, & Aust, ). The study by Zorlu et al showed a positive correlation between serum levels of 25(OH) D and vaspin in obese women (Zorlu et al, ). Omentin is another adipocytokine (Yang et al, ) that is released by visceral adipose tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation